Parental Involvement in Cultivating Local Cultural Values: A Perspective on Education - Dinnisa Haura Zhafira Hidayat; Aghnia Eridani Alamudin Putri; Falih Ariq Rozano; Asy'ari Muhammad Fahmi; Citra Ayu Maharani Permatasuri; Fathan Mubiyna; Valiant Zahirul Azmi; Yasmina Azfa Putri Alif (Universitas Cokroaminoto Palopo, 2024)
Indonesia is rich in various cultural arts and traditions, with each region boasting its own diverse cultural heritage. However, the pervasive influence of globalization has spurred the erosion of these valued traditions, leading to significant cultural shifts. Recognizing this trend, there is an urgent call for parents to play a pivotal role in safeguarding local culture, particularly by instilling it in their children. This imperative underscores the need to understand the extent of parental influence on cultural preservation amidst globalization's invasion, the impact of western culture on indigenous traditions, factors shaping a child's adherence to local cultural values, parental strategies to counter foreign cultural influences, and the process of transmitting cultural heritage to the younger generation. Through a cross-sectional study conducted in Pasir Muncang Village, Purwakarta, Indonesia, this research delves into these dynamics. Employing qualitative analysis of interview data, the study reveals that parents indeed wield substantial influence in upholding cultural traditions. Their efforts serve as a barricade against the invasion of external cultures, ensuring the continuity of indigenous heritage. These findings illuminate the pivotal role of parental involvement in preserving cultural identity amidst the currents of globalization.